The Affordable Care Act Survives, for Now - Hall, Mark A. (The Hastings Center report, 2012)
The new millennium is still very young, so it is too early to declare National Federation of Independent Business v. Sebelius1 the health law “case of the century,” but that title would not be hyperbolic. Never before have we seen a case of such monumental importance for how health care is financed and delivered in the United States. At the Supreme Court, no decision has been more closely watched and more anxiously awaited since Bush v. Gore in 2000. In the balance was the fate of President Obama's signature piece of domestic legislation, one that affects nearly every aspect of the largest segment of our economy, and so is perhaps the most important piece of social legislation since the New Deal. To no one's surprise, the decision was announced at the very end of the Court's term and was split five to four. What was very surprising, however, was the Court's embrace of the tax power defense of the individual mandate. And what was outright shocking was a seven-to-two majority in favor of finding the Medicaid expansion unconstitutional unless states are allowed to opt out of the expansion. The case holds great significance not only for the fate of the Patient Protection and Affordable Care Act—and, thus, for the nation's health care public policy—but also for constitutional doctrine that applies much more broadly than in the health care arena.